STRATEGI KOMUNIKASI POLITIK DALAM PENDEKATAN BUDAYA PAPUA (STUDI KASUS PEMILIHAN GUBERNUR PAPUA) - Kadir, Imam Alfian; Dirgantari, Annisagita Sungga; Sanmas, Masni; Jaya, Muhammad Nur; Arif, Muhammad (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
Political communication in Papua reflects a unique intersection between democratic modernization and traditional symbolic systems. Politics is not merely a contest for power but a medium to express cultural identity and collective legitimacy within Papuan society. This research applies a qualitative phenomenological method supported by ethnographic interviews with customary, religious, and political actors. The analysis draws upon Giddens’ structuration theory, Gudykunst’s intercultural communication framework, and Geertz’s symbolic anthropology to interpret meaning reproduction in campaign practices. The study finds that the victory of Matius-Aryoko in the 2025 gubernatorial election was shaped by their ability to embed cultural narratives, trust capital, and local symbols, such as noken and ritual gatherings, into persuasive messages. These elements transformed political campaigns into cultural performances that strengthened social cohesion and legitimacy. Political communication in Papua thus operates as a dialogic negotiation between local wisdom and the national democratic project. Candidates who successfully align symbolic representation with communal ethics gain deeper moral authority and public acceptance. Cultural-based political communication provides a transformative path for Papuan nationalism, shifting it from the periphery to the center of Indonesia’s civic discourse. Keywords: Political Communication, Cultural Legitimacy, Papua, Local Wisdom, Nationalism Transformation.